2011
DOI: 10.1038/msb.2011.66
|View full text |Cite
|
Sign up to set email alerts
|

Arabidopsis G‐protein interactome reveals connections to cell wall carbohydrates and morphogenesis

Abstract: Yeast two-hybrid technology is used to build a high-quality protein interaction network centered on Arabidopsis G-protein coupled signaling. The interactions uncovered are without precedent in animals and fungi and help identify new cellular roles for G-protein signaling in plants.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

7
172
1
9

Year Published

2013
2013
2023
2023

Publication Types

Select...
7
1
1

Relationship

0
9

Authors

Journals

citations
Cited by 192 publications
(189 citation statements)
references
References 44 publications
7
172
1
9
Order By: Relevance
“…When agb1 and agg1 agg2 mutants were inoculated with P. syringae pv tomato DC3118 by spraying, they supported a small but significant increase of P. syringae pv tomato DC3118 growth compared with the wild type, suggesting that stomatal defense could be affected in these mutants as well. In agb1 mutants, stomatal density was shown to be higher than in the wild type (Zhang et al, 2008a;Klopffleisch et al, 2011). The increased stomatal density is probably also a contributing factor to higher P. syringae pv tomato DC3118 growth in the agb1 mutants.…”
Section: Discussionmentioning
confidence: 92%
See 1 more Smart Citation
“…When agb1 and agg1 agg2 mutants were inoculated with P. syringae pv tomato DC3118 by spraying, they supported a small but significant increase of P. syringae pv tomato DC3118 growth compared with the wild type, suggesting that stomatal defense could be affected in these mutants as well. In agb1 mutants, stomatal density was shown to be higher than in the wild type (Zhang et al, 2008a;Klopffleisch et al, 2011). The increased stomatal density is probably also a contributing factor to higher P. syringae pv tomato DC3118 growth in the agb1 mutants.…”
Section: Discussionmentioning
confidence: 92%
“…Similar to AGB1, ER is also required for resistance against P. cucumerina (Llorente et al, 2005). Recently, both er and agb1 mutants were found to have altered cell wall structure (Sánchez-Rodríguez et al, 2009;Klopffleisch et al, 2011;Delgado-Cerezo et al, 2012). The similarity of the mutant phenotypes in er and agb1 mutants suggests that AGB1 may be required for the functions of ER in the regulation of development, cell wall structure, and resistance against P. cucumerina.…”
Section: Discussionmentioning
confidence: 95%
“…These observations indicate a defect in cell division and elongation as the possible cause of gpa1 morphological phenotypes, which also could explain the short hypocotyl and open apical hook of gpa1 etiolated seedlings (Lease et al, 2001;Ullah et al, 2002Ullah et al, , 2003. Interestingly, the assembly of a G-protein interactome has revealed that GPA1 interacts with proteins that are involved in the modulation of cell wall composition or structure (Klopffleisch et al, 2011), like those we reported misregulated in the adt3 proteome (Table I), providing a possible link between G-proteins and morphogenesis. ADT3 is part of a signaling module that includes GPA1 and GCR1, whose activation by blue light leads to Phe synthesis (Warpeha et al, 2006(Warpeha et al, , 2008.…”
Section: Adt3 In Signaling and Developmentmentioning
confidence: 98%
“…Experimental PPIs of CORNET consist of data retrieved from BIND (Bader et al, 2003), IntAct (Hermjakob et al, 2004), BioGRID (Stark et al, 2006), DIP (Salwinski et al, 2004), MINT (Chatr-aryamontri et al, 2007), TAIR (Rhee et al, 2003), Arabidopsis Interactome Mapping (Arabidopsis Interactome Mapping Consortium, 2011), MIND 0.5 (Lalonde et al, 2010), and the G-protein interactome (Klopffleisch et al, 2011). Predicted PPIs were not considered in this study.…”
Section: Cornet 20 Datamentioning
confidence: 99%